根室アイヌにおける家構成員の流動性のメカニズム－対処流動と予備流動－ - 遠藤, 匡俊 (社団法人 東京地学協会, 1996)
Many old documents show that the Ainu in the Edo period (1603-1867), who were fishers, hunters and gatherers, were a migratory people. It is also widely accepted that the Ainu moved seasonally from their home residences. This probably indicates that the residents of these settlements were relatively stable. But a detailed analysis of other documents shows that two types of mobility were found in Ainu society : inter-settlement movement of households and inter-household movement of the inhabitants. In the Takashima district during the years 1834-1871, the high death rate was the main cause for inter-household movement of the inhabitants. This type of mobility is entitled “Coping Mobility”. The purpose of this paper is to show that during the years 1848-1858 the composition of households in the Nemuro district of Hokkaido varied as a result of inter-household movement of its members, and the main cause for the high mobility was not the high death rate but the high divorce rate. In the Nemuro district, the population of the Ainu decreased dramatically between 1848 and 1852, and then it increased between 1852 and 1858 (Figs. 1 and 2). Their life had already changed depending less on fishing, hunting, and gathering, under the influence of the Wajin. Most permanent residences were located within the same settlements (Fig. 3), but many resident members moved between households (Fig. 4). The number of persons per 100 inhabitants during a 10-year period who moved between households was very large, especially in the Nemuro district and also in the Takashima and Monbetsu districts. But the number was much smaller in the Mitsuishi and Shizunai districts and the southwestern part of Sakhalin (Table 1). The stability of the household members was much lower in the Nemuro, Takashima and Monbetsu districts than in the Shizunai district and the southwestern part of Sakhalin (Fig. 5). Four factors were recognized as main causes for the movement of household members : (1) the death of a spouse, (2) the death of someone other than a ...